Characterization of Rice Homeobox Genes, OsHOX22 and OsHOX24, and Over-expression of OsHOX24 in Transgenic Arabidopsis Suggest Their Role in Abiotic Stress Response - Bhattacharjee, Annapurna; Khurana, Jitendra P.; Jain, Mukesh (Frontiers in Plant Science, 2016)
Homeobox transcription factors are well known regulators of plant growth and development. In this study, we carried out functional analysis of two candidate stress-responsive HD-ZIP I class homeobox genes from rice, OsHOX22 and OsHOX24. These genes were highly upregulated under various abiotic stress conditions at different stages of rice development, including seedling, mature and reproductive stages. The transcript levels of these genes were enhanced significantly in the presence of plant hormones, including abscisic acid (ABA), auxin, salicylic acid and gibberellic acid. The recombinant full-length and truncated homeobox proteins were found to be localized in the nucleus. Electrophoretic mobility shift assay established the binding of these homeobox proteins with specific DNA sequences, AH1 (CAAT(A/T)ATTG) and AH2 (CAAT(C/G)ATTG). Transactivation assays in yeast revealed the transcriptional activation potential of full-length OsHOX22 and OsHOX24 proteins. Homo- and hetero-dimerization capabilities of these proteins have also been demonstrated. Further, we identified putative novel interacting proteins of OsHOX22 and OsHOX24 via yeast-two hybrid analysis. Over-expression of OsHOX24 imparted higher sensitivity to stress hormone, ABA, and abiotic stresses in the transgenic Arabidopsis plants as revealed by various physiological and phenotypic assays. Microarray analysis revealed differential expression of several stress-responsive genes in transgenic lines as compared to wild-type. Many of these genes were found to be involved in transcriptional regulation and various metabolic pathways. Altogether, our results suggest the possible role of OsHOX22/OsHOX24 homeobox proteins as negative regulators in abiotic stress responses.